Do engineering master's students know what they don't know?: Exploring abstracting & indexing service use and non-use. Issue 1 (2nd February 2015) - Johnson, Paula C; Simonsen, Jennifer E.
Abstract : Purpose: – The purpose of this study was to determine whether engineering master's students at a medium-sized university use library-provided abstracting and indexing (A&I) services (e.g. Compendex), and if they do, to what extent, in what manner and for what purposes. Design/methodology/approach: – A mixed methodology approach was used to explore electronic information-seeking patterns of engineering master's students at New Mexico State University. Usage statistics, a focus group and a Web-based survey were used, the latter composed of 17 questions using a critical incident approach and direct questions to probe: reasons for and method of search, types of materials used (with relative frequencies), means of obtaining materials and evaluations of the usefulness of five library-provided A&I services. Findings: – Only 15 per cent of respondents used a subscription A&I service such as Compendex when searching specific terms. The majority of sources used were located through known term searches, and master's learned of these information resources through article citations or conversations with colleagues. Half the respondents reported using Google Scholar to find the last scholarly article they had read. Engineering master's students – similar to practicing engineers – evaluate the costs associated with obtaining information, and may "satisfice". Even so, students expressed interest in increasing their knowledge of skills and strategies to find worthwhile electronic information. Originality/value: – This study sheds light on engineering master's students' use of A&I services, and examines their perceptions of five of these services commonly provided by academic libraries.